2011
DOI: 10.1111/j.1365-2222.2011.03776.x
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and airway disease

Abstract: Epidemiological and toxicological research continues to support a link between urban air pollution and an increased incidence and/or severity of airway disease. Detrimental effects of ozone (O(3)), nitrogen dioxide (NO(2)) and particulate matter (PM), as well as traffic-related pollution as a whole, on respiratory symptoms and function are well documented. Not only do we have strong epidemiological evidence of a relationship between air pollution and exacerbation of asthma and respiratory morbidity and mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
271
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(286 citation statements)
references
References 158 publications
(190 reference statements)
4
271
3
8
Order By: Relevance
“…Diesel exhaust particles (DEPs), composed of 80% ultrafine particles, and associated polycyclic aromatic hydrocarbons impact on airborne allergens, increasing exposure effects, concentration and allergenic biological activity [38]. Several studies have demonstrated effects of ozone over respiratory symptoms, including shortness of breath, wheezing and coughing, lower respiratory tract infections, acute and transient decreases in lung function, increased airway responsiveness, airway injury and inflammation, and systemic oxidative stress [39].…”
Section: Pollen and Mould Allergymentioning
confidence: 99%
“…Diesel exhaust particles (DEPs), composed of 80% ultrafine particles, and associated polycyclic aromatic hydrocarbons impact on airborne allergens, increasing exposure effects, concentration and allergenic biological activity [38]. Several studies have demonstrated effects of ozone over respiratory symptoms, including shortness of breath, wheezing and coughing, lower respiratory tract infections, acute and transient decreases in lung function, increased airway responsiveness, airway injury and inflammation, and systemic oxidative stress [39].…”
Section: Pollen and Mould Allergymentioning
confidence: 99%
“…Intense energy consumption, together with industrial and transportation emissions, has led to population exposure to a diverse variety of unhealthy concentrations of air pollution, leading to increased morbidity and mortality primarily due to cardiovascular and respiratory causes (1). Vulnerable groups include patients with chronic obstructive pulmonary disease (COPD), which is currently the fourth leading cause of death worldwide (2).…”
mentioning
confidence: 99%
“…For adult male and female patients, the total weight of the chemical variables in the occurrence of asthma ER visits is higher in the pollen season of Ambrosia compared to the pollen-free season (Table 2). Some studies found that exposure to outdoor air pollutants may increase the risk of allergic airway diseases [11,[55][56][57][58]. This may be explained by the fact that air pollutants, especially burning of fossil fuels, can affect allergens.…”
Section: Discussionmentioning
confidence: 99%